2002
DOI: 10.1037/0735-7044.116.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced changes in place and response learning in young adult female rats.

Abstract: Many findings suggest that changes in circulating estrogen levels influence cognition, in some cases impairing performance and in others enhancing performance. One interpretation of these mixed effects is that estrogen biases the strategy used to solve a task. To test this idea, young adult female rats, ovariectomized for 21 days, were trained after acute hormone or control treatment in 2 very similar tasks with different cognitive requirements. One task required place learning and the other response learning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
187
8
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(211 citation statements)
references
References 90 publications
15
187
8
1
Order By: Relevance
“…Within 48 h of administering 17β-estradiol, CA1 spine density increases and these maximal levels are maintained for an additional 48 h after estrogen is metabolized, then density slowly declines over the next few days (Woolley and McEwen, 1993;Woolley, 1998). While the 17β-estradiol dose used in this study (0.1 mL of 5 μg) is similar to that which has been used in other behavioral paradigms (Chesler and Juraska, 2000;Korol and Kolo, 2002), this dose is too low to fully reproduce increases in CA1 apical spine density which have been demonstrated in morphological studies (0.1 mL of 10 μg; Gould et al, 1990;Woolley and McEwen, 1993;Woolley, 1998). Therefore, estrogen treatments used in future research will need to include higher doses in order to determine a more clear relationship between changes in the brain and subsequent behavior.…”
Section: The Lack Of An Estrogen Influence On Hippocampal Morphology mentioning
confidence: 88%
See 2 more Smart Citations
“…Within 48 h of administering 17β-estradiol, CA1 spine density increases and these maximal levels are maintained for an additional 48 h after estrogen is metabolized, then density slowly declines over the next few days (Woolley and McEwen, 1993;Woolley, 1998). While the 17β-estradiol dose used in this study (0.1 mL of 5 μg) is similar to that which has been used in other behavioral paradigms (Chesler and Juraska, 2000;Korol and Kolo, 2002), this dose is too low to fully reproduce increases in CA1 apical spine density which have been demonstrated in morphological studies (0.1 mL of 10 μg; Gould et al, 1990;Woolley and McEwen, 1993;Woolley, 1998). Therefore, estrogen treatments used in future research will need to include higher doses in order to determine a more clear relationship between changes in the brain and subsequent behavior.…”
Section: The Lack Of An Estrogen Influence On Hippocampal Morphology mentioning
confidence: 88%
“…Acute estrogen replacement can be given 3 weeks to 4 months after OVX to observe changes in memory (Korol and Kolo, 2002;Sandstrom and Williams, 2004). Administering 17β-estradiol to OVX females either 72 and 48 h, or 48 and 24 h before behavioral assessment, which is consistent with our time frame, can either improve or impair spatial memory, depending on the task, compared with controls (Frye, 1995;Sandstrom and Williams, 2001;Korol and Kolo, 2002). Perhaps our handling procedure may have negated estrogen's effects on the Y-maze because of the enriched setting.…”
Section: The Lack Of An Estrogen Influence On Hippocampal Morphology mentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol regulates PFC blood flow in humans (Berman et al 1997), and Korol (2002;2004) has demonstrated that E2 biases toward or against the activation of circuits mediating different forms of cognition: high estrogen favoring place-activated learning and low estrogen levels response-dependent learning. It is tempting to speculate, therefore, that disturbed ER alpha signaling in the luteal phase may interact with decreased PFC efficiency in those with the Val/ Val genotype so as to permit the expression of a dysphoric state suggestive of disinhibited subcortical (e.g., amygdala) activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because the hippocampus has been demonstrated to be one of the main hormone-sensitive targets in the brain, hippocampus dependent cognitive functions, such as spatial-memory tasks, were investigated. Results are mixed, showing differences in associations to endogenous and exogenous hormonal variation, dose-and durationspecific reactions, and interactions between different gonadal hormones on cognitive functions (e.g., Bimonte and Denenberg, 1999;Chesler and Juraska, 2000;Gibbs, 2000;Korol and Kolo, 2002;O'Neal et al, 1996;Stackman et al, 1997). Some studies find evidence for decreased spatial abilities (i.e., spatial learning and spatial recognition memory) in high-estrogen phases during the cycle (e.g., Galea and Kavaliers, 1995;Lacreuse et al, 2001).…”
Section: Introductionmentioning
confidence: 99%